Etiology and Clinical Outcomes of Acute Respiratory Virus Infection in Hospitalized Adults - Seo, Yu Bin; Song, Joon Young; Choi, Min Ju; Kim, In Seon; Yang, Tea Un; Hong, Kyung-Wook; Cheong, Hee Jin; Kim, Woo Joo (Infection & chemotherapy, 2014)
Etiologies and clinical profiles of acute respiratory viral infections need to be clarified to improve preventive and therapeutic strategies. A retrospective observational study at a single, university-affiliated center was performed to evaluate the respiratory viral infection etiologies in children compared to that in adults and to document the clinical features of common viral infections for adults from July 2009 to April 2012. The common viruses detected from children (2,800 total patients) were human rhinovirus (hRV) (31.8%), adenovirus (AdV) (19.2%), respiratory syncytial virus (RSV) A (17.4%), RSV B (11.7%), and human metapneumovirus (hMPV) (9.8%). In comparison, influenza virus A (IFA) had the highest isolation rate (28.5%), followed by hRV (15.5%), influenza virus B (IFB) (15.0%), and hMPV (14.0%), in adults (763 total patients). Multiple viruses were detected in single specimens from 22.4% of children and 2.0% of adults. IFA/IFB, RSV A/B, and hMPV exhibited strong seasonal detection and similar circulating patterns in children and adults. Adult patients showed different clinical manifestations according to causative viruses; nasal congestion and rhinorrhea were more common in hRV and human coronavirus (hCoV) infection. Patients with RSV B, hRV, or AdV tended to be younger, and those infected with RSV A and hMPV were likely to be older. Those with RSV A infection tended to stay longer in hospital, enter the intensive care unit more frequently, and have a fatal outcome more often. The bacterial co-detection rate was 26.5%, and those cases were more likely to have lower respiratory tract involvement (P = 0.001), longer hospital stay (P = 0.001), and higher mortality (P = 0.001). The etiologic virus of an acute respiratory infection can be cautiously inferred based on a patient's age and clinical features and concurrent epidemic data. Large-scale prospective surveillance studies are required to provide more accurate information about respiratory viral infection etiology, which could favorably influence clinical outcomes.